2014
DOI: 10.1007/s10661-014-3666-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial trends in water quality of Lake Taihu, China: analysis from a north to mid-lake transect, 1991–2011

Abstract: Interpretations of state and trends in lake water quality are generally based on measurements from one or more stations that are considered representative of the response of the lake ecosystem. The objective of this study is to examine how these interpretations may be influenced by station location in a large lake. We addressed this by analyzing trends in water quality variables collected monthly from eight monitoring stations along a transect from the central lake to the north in Lake Taihu (area about 2,338 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Therefore, the inter-annual variations of water quality were under the dual influence of hydrological conditions (e.g., water level, discharge) and sewage flowed into the lake. Eutrophication remains one of the most pervasive environmental problems in lakes [23]. The nutrient indicators considered in the present study all showed significant seasonal variations.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Therefore, the inter-annual variations of water quality were under the dual influence of hydrological conditions (e.g., water level, discharge) and sewage flowed into the lake. Eutrophication remains one of the most pervasive environmental problems in lakes [23]. The nutrient indicators considered in the present study all showed significant seasonal variations.…”
Section: Discussionmentioning
confidence: 50%
“…Dilution was identified as the controlling factor that drives the seasonal variability in the water quality of Poyang Lake. Eutrophication remains one of the most pervasive environmental problems in lakes [23]. The nutrient indicators considered in the present study all showed significant seasonal variations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Over the past several decades, harmful algae blooms (HABs) have frequently occurred worldwide, causing serious ecological and economic impacts to aquatic ecosystems and human health (Akyuz et al, 2014;Paerl and Huisman, 2008). Several chemical (Burson et al, 2014;Fan et al, 2013), mechanical and biological techniques (Kim et al, 2007;Nan et al, 2008) have been developed to reduce these impacts.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand, monitor, and manage the water resources, researchers are required to measure the water quality parameters regularly at diverse locations over different periods (Atkinson & Mabe 2006;Carraro et al 2012;Zhang et al 2015). Long term site studies (Akyuz et al 2014;Su et al 2015;Wang et al 2015;Yan et al 2016) and satellite imagery (Nellis et al 1998;Bergamino et al 2010;Pu et al 2017) have shown evidence of spatiotemporal dynamics in water quality variables in lake environments. Human activities (Warnken & Buckley 2004;Krogh et al 2009), urbanisation and land use (Ahearn et al 2005;Almeida et al 2007;Zhao et al 2013;Kändler et al 2017) have been reported to affect water quality in catchments and rivers.…”
Section: Introductionmentioning
confidence: 99%